STEADY-STATE ANALYSIS OF CROSS-HOLE PNEUMATIC INJECTION TESTS IN UNSATURATED FRACTURED TUFF - Illman W.A.; Neuman S.P. (My University, 2003)
Numerous single-hole and cross-hole pneumatic injection tests have been conducted in unsaturated fractured tuff at the Apache Leap Research Site (ALRS) near Superior, Arizona. Steady-state analyses of single-hole tests conducted by Guzman et al. [Summary of Air Permeability Data From Single-Hole Injection Tests in Unsaturated Fractured Tuffs at the Apache Leap Research Site: Results of Steady-State Test Interpretation (1996)] have yielded values of air permeability at various locations throughout the tested rock volume on nominal scales from 0.5 to 3.0 m. Analyses of transient data from single-hole and larger-scale cross-hole tests were performed by Illman and Neuman [Ground Water 38 (2000) 899; Water Resour. Res. 37 (2001) 583] using type-curves and by Vesselinov and Neuman [Ground Water 39 (2001) 685] and Vesselinov et al. [Water Resour. Res. 37 (2001a) 3001; Water Resour. Res. 37 (2001b) 3041] using numerical inversion. These have yielded bulk fracture permeabilities and porosities on scales ranging from a few meters to several tens of meters. We complement the latter results by steady-state analysis of a relatively large set of cross-hole tests. Steady-state analysis (a) allows interpreting cross-hole tests that were not interpreted using type-curves due to weak or noisy signals, (b) is relatively easy to perform, and (c) yields results comparable with those obtained from transient analyses. We analyze the results statistically and discuss their implications vis-a-vis the pneumatic properties of unsaturated fractured tuff at the ALRS. Our results strengthen the evidence for a previously surmised permeability scale effect at the site.
Keywords: PERMEABILITY; FRACTURES; TUFF; TOMOGRAPHY; UNSATURATED ZONE; STATISTICAL ANALYSIS